2009
DOI: 10.3171/2008.10.jns081141
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase as a new target for malignant glioma therapy

Abstract: These findings suggest that the robust IDO expression with rapid consumption of Trp in human glioma cells induced by IFN-gamma could lead to immune resistance in glioma cells. Indoleamine 2,3-dioxygenase inhibitors that prevent Trp depletion could be used with anticancer drugs to improve therapeutic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 25 publications
3
52
0
1
Order By: Relevance
“…Constitutive IDO-1 expression has been shown in 9 of 10 human glioblastoma biopsies (8) and in brain tumor cell lines (50). It is also known that IDO-1 activity in human glial and malignant glioma cell lines is increased by IFN-g (50). Thus, expression of IDO-1 in brain tumor cells is likely to be triggered when IFN-g is produced from activated T cells and/or microglia and neurons.…”
Section: Initiation Of Antitumor Immune Responses: Key Mechanisms Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Constitutive IDO-1 expression has been shown in 9 of 10 human glioblastoma biopsies (8) and in brain tumor cell lines (50). It is also known that IDO-1 activity in human glial and malignant glioma cell lines is increased by IFN-g (50). Thus, expression of IDO-1 in brain tumor cells is likely to be triggered when IFN-g is produced from activated T cells and/or microglia and neurons.…”
Section: Initiation Of Antitumor Immune Responses: Key Mechanisms Andmentioning
confidence: 99%
“…56). Constitutive IDO-1 expression has been shown in 9 of 10 human glioblastoma biopsies (8) and in brain tumor cell lines (50). It is also known that IDO-1 activity in human glial and malignant glioma cell lines is increased by IFN-g (50).…”
Section: Initiation Of Antitumor Immune Responses: Key Mechanisms Andmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies of iDo inhibitors against GBM have been carried out and these agents do show some activity as single agents. Miyazaki et al showed the iDo inhibitor 1-methyl L-tryptophan (1MT) prevented tryptophan consumption and suppressed the growth of LN 229 glioma cells (192). Hanihara et al reported 1MT significantly suppressed tumor growth in a murine glioma model.…”
Section: Inhibitors Of the Kynurenine Pathwaymentioning
confidence: 99%
“…The inhibition of IDO expression could significantly suppress tumor growth and promote the anti-tumor activities of various immunotherapeutic agents in relevant animal models (11,12). More importantly, previous studies of our group have reported that IFN-γ induces the expression of IDO via the Janus kinase/ signal transducer and activator of transcription 1 (JAK/STAT1) signaling pathway (13,14).…”
Section: Introductionmentioning
confidence: 99%